Lncrna nonratt021477.2 interference aggravates h2o2-induced oxidative stress in brl cells - Hong JI; Yue HUA; Chun-Wei LIU; Zi-Yi SHAO; Jia-Jun ZHANG; Shui-Qing YU (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Long non-coding RNA (lncRNA) plays important biological regulatory functions at different levels. lncRNA NONRATT021477.2 (lncRNA77.2) was identified as a key gene under cold stress conditions in rats. From the literature, lncRNA77.2 may have important roles during antioxidant, but this conjecture requires investigation. To address this knowledge gap, we investigated the effects of lncRNA77.2 interference on H2O2- induced oxidative stress in rat liver cells (Buffalo rat liver, BRL).In the current study, H2O2 treatment simulated BRL cell oxidative stress. H2O2 treatment led to a significant increase in oxidative stress levels in BRL cells, whereas the gene expression levels of antioxidase and lncRNA 77.2 and cell viability were significantly reduced. Additionally, the expression of Nrf2 and Keap1 proteins decreased significantly compared to the control group. BRL cells were transfected with antisense oligonucleotides (ASO) or a negative control ASO (ASO-NC) and then treated with H2O2. The results showed lncRNA77.2 interference increased oxidative stress levels, reduced gene expression of antioxidant enzymes, Nrf2 and Keap1 expression levels. The results indicated that lncRNA77.2 interference aggravated H2O2-induced oxidative stress in BRL cells, which suggested that lncRNA77.2 is an antioxidant factor that plays an important role in the regulation of oxidative stress in BRL cells.